Avaliação das capacidades físicas e saúde mental de adolescentes infectados com a COVID e os não infectados - Dantas, Dayane Nunes (2023)
The Coronavirus virus was discovered decades ago and since then has been causing a series of problems for the health of the population. Among the epidemics caused by the virus, the 2020 pandemic was the longest and the one that caused the most damage compared to previous ones, several consequences are pointed out in the literature due to the development of the COVID-19 disease, consequences that can affect physical capacities. The objective of this study was to verify the effect of COVID19 on the physical capacity, level of physical activity and mental health of adolescents aged 12 to 18 years. Method: this is a cross-sectional and quantitative study. After going through an initial screening, the adolescents were divided into two groups, anthropometry was verified, they answered two questionnaires: the depression, anxiety and stress scale for adolescents and the habitual physical activity questionnaire. Then they participated in motor tests: speed, upper limb strength, lower limb strength, agility, flexibility and abdominal strength. Result: A total of 123 subjects, 63 women, 60 men, participated in the study. Applied the Student's t-Test, a significant difference was found in the variable strength in the abdominal region (p= 0.039 and 0.040) and in the horizontal impulsion test (p= 0.023 and 0.023). When applying the Chi-square, an association was observed between lower performance in physical capacity and strength in the abdominal test [x² (3) = 8.105; p = 0.044]. Binary logistic regression showed that the difference was not statistically significant to interfere with the physical abilities of adolescents and a small negative correlation was found between COVID-19 and abdominal strength (rô = -0.226; p= 0.012). The MannWhitney showed that having Covid-19 has no effect on the depression variables (U=1840.00; p= 0.7); in anxiety (U= 1750.50; p= 0.3); and stress (U= 1738.00; p= 0.3). Conclusion: no differences were found in physical abilities, level of physical activity and mental health between groups.